Проблемы и последствия государственного долга для социально–экономической безопасности Украины - Карпухно, И.А.; Майданюк, А.А. (Культура народов Причерноморья, 2014)
В статье проанализирована динамика внутреннего и внешнего государственного долга
Украины, особенности изменения его структуры за последние годы. Обозначены социально–
экономические, внешнеполитические предпосылки формирования внутреннего и внешнего
государственного долга. Рассмотрены последствия увеличения государственного долга для социально–
экономической безопасности в стране. Предложена концепция управления государственным долгом
Украины, а также пути его погашения с учетом современного опыта управления государственным
долгом в развитых странах. Рассмотрены принципы, критерии и направления повышения
эффективности управления государственным долгом Украины. У статті проаналізовано динаміку внутрішнього та зовнішнього державного боргу України,
особливості зміни його структури за останні роки. Позначені соціально–економічні, зовнішньополітичні
передумови формування внутрішнього й зовнішнього державного боргу. Розглянуті наслідки збільшення
державного боргу для соціально–економічної безпеки в країні. Запропонована концепція управління
державним боргом України, а також шляхи його погашення з урахуванням сучасного досвіду управління
державним боргом у розвинених країнах. Розглянуті принципи, критерії та напрямки підвищення
ефективності управління державним боргом України. The dynamics of the internal and external public debt of Ukraine, the features of changes of its
structure in recent years are analyzed in the article. Socio–economic, foreign policy prerequisites of forming of
an internal and external public debt are designated. The consequences of a public debt’s increase for social and
economic security in the country are considered. The management concept by a public debt of Ukraine, and also
a way of its settlement taking into account modern experience of national debt management in developed
countries is offered. The principles, criteria and the directions of effectiveness increase of Ukrainian public
debt's management are examined. Under the creation of socially oriented model of economy, the problem of
servicing of a public debt of Ukraine is one of key for macroeconomic stability and socio–economic country
situation. In the course of efficient debt strategy’s forming for ensuring socio–economic security of the state,
implementation of the following measures is necessary to ensure an effective use of state loans on the investment
purposes, instead of on consumption; to strengthen a role of internal market loans in the course of financing of a
budget deficit of rather external; to reduce a share of foreign currency in a public debt; to improve system of
forecasting of all block of the interconnected indicators which have direct influence on forming of a public debt
of Ukraine; to raise a level of information and analytical providing debt policy.